Collaborative Governance Process in MSMEs Empowerment through Desa-Preneur Program in Sidoarum Village, Yogyakarta - Trisnantari, Sita Agung; Susilastuti, Dewi Haryani; Putri, Tri Winarni Soenarto (Populasi, 2023)
Rural MSMEs have a small business scale in terms of capital, labor, market orientation, and limited technology adoption so Dinas Koperasi and UKM DIY (Department of Cooperatives and SMEs of the Special Region of Yogyakarta) implement MSMEs empowerment policy through the Desa-Preneur Program. The involvement of various stakeholders has been attempted, but this program has not fully targeted all Sidoarum MSME actors. This study discusses the process of collaborative governance in the implementation of the Desa-Preneur Program in Sidoarum Village, Yogyakarta. The research uses a qualitative descriptive method with primary data obtained from interviews, and secondary data collected through documentation and literature. The result showed that collaborative governance indicators have not been fully implemented. The role of lurah as program leader has not been maximized in carrying out the role as a program leader. Not all MSMEs actors participate in mentoring routinely and village economic institutions have not been formed. Several program achievements have been fulfilled, but still require consistent implementation of learning outcomes. The researchers suggest that village government to have more concern bridging out the provincial government and community in term of Desa-Preneur Program implementation. Institutional strengthening of BUMDes and cooperatives is important as a place of collaboration between stakeholders. Desa-Preneur Program in Sidoarum Village must be synergized with other programs and needs to involve other government institutions that support local MSMEs empowerment.